A high thermal conductivity nylon material and preparation method thereof

By adopting a collaborative design of a dual-matrix system and high-thermal filler in nylon materials, combined with the addition of antioxidants and light stabilizers, the problems of low thermal conductivity and aging of conventional nylon materials are solved, and the improvement of high thermal conductivity and anti-aging performance is achieved.

CN119752169APending Publication Date: 2025-04-04JIANGSU FUXIDAO NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510061187.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Conventional nylon materials have low thermal conductivity, and as the thermal conductivity continues to increase, aging is prone to occur, resulting in deterioration of material properties.

Method used

Nylon 6 and polybutylene terephthalate were used as bimatrix, aluminum nitride and carbon nanotubes were added as high thermal conductivity fillers, and pretreated, antioxidants, light stabilizers and compatibilizers were added to build efficient thermal conductivity channels and improve material aging performance.

Benefits of technology

It significantly improves the thermal conductivity and anti-aging properties of the material, enhances the mechanical properties, and meets the high performance and multifunctional needs of modern industry for nylon materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752169A_ABST
    Figure CN119752169A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, and in particular to a high thermal conductivity nylon material and a preparation method thereof. The material comprises the following raw materials in parts by weight: 100 parts of nylon, 20-30 parts of polybutylene terephthalate, 17-24 parts of high thermal conductivity filler, 0.8-1.3 parts of antioxidant, 0.3-0.5 parts of light stabilizer, 3-5% of the total mass of nylon and polybutylene terephthalate in a compatibilizer dosage, and 1-2% of the high thermal conductivity filler in a coupling agent dosage; the high thermal conductivity filler is composed of 15-20 parts of aluminum nitride and 2-4 parts of carbon nanotubes; in the present scheme, by adopting a collaborative design method of a double matrix, a multi-component auxiliary agent and a filler, a significant improvement in the comprehensive performance of the high thermal conductivity nylon material is achieved, aluminum nitride and carbon nanotubes are added as high thermal conductivity fillers, aluminum nitride has a high thermal conductivity, and carbon nanotubes have both excellent thermal conductivity and mechanical reinforcement performance, and are uniformly dispersed in the double matrix after pretreatment, effectively constructing a thermal conduction channel, and greatly improving the thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a high thermal conductivity nylon material and a preparation method thereof. Background Art

[0002] Polyamide, commonly known as nylon, is a general term for thermoplastic resins containing repeating amide groups -[NHCO]- on the main chain of the molecule. Polyamide is non-toxic, lightweight, wear-resistant, has good corrosion resistance and mechanical strength, and is therefore widely used in machinery, chemical industry, instrumentation, automobile and other fields.

[0003] Conventional nylon materials have low thermal conductivity and cannot transfer heat quickly and effectively. In scenarios with high heat dissipation requirements such as electronic equipment, it is easy for the equipment to accumulate heat, resulting in performance degradation and shortened life. Secondly, as the thermal conductivity continues to increase, it is prone to aging during long-term use due to environmental factors such as light, oxygen, and temperature changes, causing gradual deterioration of material performance and reducing product service life and reliability.

[0004] To this end, the present invention proposes a high thermal conductivity nylon material and a preparation method thereof. By selecting nylon 6 and polybutylene terephthalate (PBT) to form a dual matrix system, the basic performance of the material is improved by utilizing the complementary performance of the two. High thermal conductivity fillers such as aluminum nitride and carbon nanotubes are added and pretreated to construct an efficient thermal conduction channel, thereby achieving a significant improvement in thermal conductivity. At the same time, additives such as antioxidants, light stabilizers and compatibilizers are added to inhibit material aging and improve the interface compatibility between components, thereby achieving enhancement of the material's anti-aging performance and mechanical properties, thereby meeting the modern industry's demand for high performance and multifunctional nylon materials. Summary of the invention

[0005] Technical problem to be solved: Conventional nylon materials have low thermal conductivity, and as the thermal conductivity continues to increase, they are prone to aging.

[0006] In view of the deficiencies in the prior art, the present invention provides a high thermal conductivity nylon material and a preparation method thereof, thereby solving the technical problems mentioned in the background technology.

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] A high thermal conductivity nylon material comprises the following raw materials in parts by weight:

[0009] 100 parts of nylon, 20-30 parts of polybutylene terephthalate, 17-24 parts of high thermal conductive filler, 0.8-1.3 parts of antioxidant, 0.3-0.5 parts of light stabilizer, 3-5% of the total mass of nylon and polybutylene terephthalate, and 1-2% of the coupling agent of the high thermal conductive filler;

[0010] The high thermal conductive filler is composed of 15-20 parts of aluminum nitride and 2-4 parts of carbon nanotubes;

[0011] The antioxidant is composed of 0.5-0.8 parts of hindered phenol antioxidant AO-80 and 0.3-0.5 parts of phosphite antioxidant 121;

[0012] The light stabilizer is selected from hindered amine light stabilizer 944;

[0013] The compatibilizer is maleic anhydride grafted polypropylene;

[0014] The coupling agent is silane coupling agent KH560 ethanol solution.

[0015] In a possible implementation, a method for preparing a high thermal conductivity nylon material is applied to the above-mentioned high thermal conductivity nylon material, and includes the following method steps:

[0016] S1. Filler pretreatment:

[0017] S1-1, placing aluminum nitride and carbon nanotubes in a vacuum drying oven respectively, and drying at 120-130° C. for 6-8 hours to remove moisture;

[0018] S1-2, prepare a 1-2% by weight silane coupling agent KH560 ethanol solution, add the dried aluminum nitride and carbon nanotubes thereto respectively, and ultrasonically disperse for 45-60 minutes to make the coupling agent evenly coated on the surface of the filler, and then dry at 80-90° C. for 8-10 hours to obtain a pretreated filler;

[0019] S2. Premixing of base and additives:

[0020] S2-1, drying the nylon slices and the polybutylene terephthalate slices in a blast drying oven to remove moisture;

[0021] S2-2, weigh the dried nylon, polybutylene terephthalate, pretreated filler, antioxidant, light stabilizer and compatibilizer according to the proportion, add them into a high-speed mixer, and mix them at a speed of 600-800 r / min for 15-20 min to preliminarily mix the components evenly;

[0022] S3, melt blending: adding the premixed materials into a twin-screw extruder for melt blending;

[0023] S4, granulation and molding: the material extruded from the twin-screw extruder is water-cooled and drawn into a pelletizer for granulation to obtain pellets of high thermal conductivity and anti-aging nylon composite materials.

[0024] In a possible implementation, in the step S2-1, nylon is dried at 90-100° C. for 8-10 h, and polybutylene terephthalate is dried at 110-120° C. for 6-8 h.

[0025] In a possible implementation, in the S3 step, the temperature of the twin-screw extruder is set to: zone 1 temperature 230-240°C, zone 2 temperature 240-250°C, zone 3 temperature 250-260°C, zone 4 temperature 260-270°C, zone 5 temperature 270-280°C, head temperature 260-270°C, screw speed 300-400r / min, and the material residence time in the extruder is about 4-6min.

[0026] Beneficial effects compared with the prior art:

[0027] In this scheme, the comprehensive performance of high thermal conductivity nylon materials is significantly improved by adopting a collaborative design of dual matrix and multiple additives and fillers. Nylon and polybutylene terephthalate are selected as dual matrixes. Nylon has good toughness, and polybutylene terephthalate has high thermal stability and chemical stability. The combination of the two lays a solid foundation for the material. At the same time, aluminum nitride and carbon nanotubes are added as high thermal conductivity fillers. Aluminum nitride has high thermal conductivity, and carbon nanotubes have both excellent thermal conductivity and mechanical reinforcement properties. After pretreatment, they are evenly dispersed in the dual matrix, effectively constructing a thermal conduction channel, greatly improving the thermal conductivity.

[0028] In addition, hindered phenol antioxidant AO-80, phosphite antioxidant 121 and hindered amine light stabilizer 944 work together to inhibit the oxidation and photodegradation of the material and significantly enhance the anti-aging performance. Maleic anhydride grafted polypropylene acts as a compatibilizer to improve the interfacial compatibility between different components, making the internal structure of the material more stable and improving the mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings.

[0030] Figure 1 The present invention is a flow chart of the steps of a method for preparing a high thermal conductivity nylon material. DETAILED DESCRIPTION

[0031] Preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. However, the present invention can also be implemented in various forms, so the present invention is not limited to the embodiments described below.

[0032] The technical solution in the embodiment of the present application is to solve the problems of the above-mentioned background technology, and the overall idea is as follows:

[0033] Embodiment 1:

[0034] This embodiment introduces a method for preparing a high thermal conductivity nylon material, comprising the following steps:

[0035] S1. Raw material preparation: weigh 100 g nylon 6 slices, 25 g polybutylene terephthalate slices, 18 g aluminum nitride, 3 g carbon nanotubes, 0.6 g antioxidant AO-80, 0.4 g antioxidant 121, 0.4 g light stabilizer 944, 4.2 g compatibilizer maleic anhydride grafted polypropylene (calculated based on 4% of the total mass of nylon 6 and polybutylene terephthalate), 150 mL of silane coupling agent KH560 ethanol solution;

[0036] S2. Filler pretreatment:

[0037] S2-1, drying aluminum nitride and carbon nanotubes in vacuum at 125°C for 7h respectively;

[0038] S2-2, adding the dried aluminum nitride and carbon nanotubes to the silane coupling agent KH560 ethanol solution respectively, ultrasonically dispersing for 50 minutes, and then drying at 85° C. for 9 hours to obtain a pretreated filler;

[0039] S3, premixing of base and additives:

[0040] S3-1, drying the nylon 6 slices at 95°C for 9 hours and the polybutylene terephthalate slices at 115°C for 7 hours;

[0041] S3-2, adding the above raw materials into a high-speed mixer, and mixing at a speed of 700 r / min for 18 min;

[0042] S4, melt blending: the premixed materials are added into a twin-screw extruder, and melt blending is performed according to the temperature settings of 235°C for zone 1, 245°C for zone 2, 255°C for zone 3, 265°C for zone 4, 275°C for zone 5, and 265°C for die head, and the screw speed is 350r / min. The materials stay in the extruder for about 5min;

[0043] S5, granulation and molding: After water-cooled drawing, the pellets are cut into pellets, and after the pellets are dried, the specimens are prepared by injection molding, with a barrel temperature of 260°C, a mold temperature of 80°C, an injection pressure of 90MPa, a holding pressure of 70MPa, and a holding time of 15s.

[0044] Comparative Example 1:

[0045] S1. Raw material preparation: weigh 100g nylon slices, 18g boron nitride, 4g graphene, 0.4g primary antioxidant 1010, 0.4g secondary antioxidant 168, 0.66g silane coupling agent KH550 (calculated based on 2% of the total mass of boron nitride and graphene);

[0046] S2. Filler pretreatment:

[0047] S2-1. After mixing boron nitride and graphene, put them into a muffle furnace and calcine them at 550° C. for 2.5 h.

[0048] S2-2, prepare 100 mL of 2.5% mass fraction of silane coupling agent KH550 ethanol solution, add the calcined filler therein, ultrasonically disperse for 45 minutes, and then dry at 85° C. for 10 hours to obtain a pretreated filler;

[0049] S3, mixing nylon with additives: drying the nylon chips at 105°C for 10 h, then adding them into a high-speed mixer together with the pretreated filler, primary antioxidant 1010 and secondary antioxidant 168, and mixing them at a speed of 900 r / min for 12 min;

[0050] S4, melt blending: add the mixed materials into a twin-screw extruder, and melt blend them according to the temperature settings of zone 1 at 255°C, zone 2 at 265°C, zone 3 at 275°C, zone 4 at 285°C, zone 5 at 285°C, die head at 275°C, and screw speed at 350r / min. The materials stay in the extruder for about 4min.

[0051] S5, granulation and molding: After water-cooled drawing, the pellets are cut into pellets to obtain pellets. After the pellets are dried, the specimens are prepared by injection molding process, with a barrel temperature of 270°C, a mold temperature of 90°C, an injection pressure of 90MPa, a holding pressure of 70MPa, and a holding time of 15s.

[0052] Comparative Example 2

[0053] S1. Raw material preparation: weigh 100g nylon slices and 10g talcum powder;

[0054] S2, mixing the matrix and the filler: drying the nylon slices at 95°C for 9 hours, then adding the dried nylon slices and talcum powder into a high-speed mixer and mixing at a speed of 700 r / min for 18 minutes;

[0055] S3, melt blending: the mixed material is added into a twin-screw extruder, and melt blending is performed according to the temperature settings of 235°C for zone 1, 245°C for zone 2, 255°C for zone 3, 265°C for zone 4, 275°C for zone 5, and 265°C for die head, and the screw speed is 350r / min. The material stays in the extruder for about 5min;

[0056] S4, granulation and molding: After water-cooling and drawing, pellets are cut into pellets. After the pellets are dried, the sample strips are prepared by injection molding, with a barrel temperature of 260°C, a mold temperature of 80°C, an injection pressure of 90MPa, a holding pressure of 70MPa, and a holding time of 15s.

[0057] Comparative experiment:

[0058] According to the preparation methods provided in the above-mentioned Example 1, Comparative Example 1 and Comparative Example 2, the nylon material finally prepared was tested:

[0059] Thermal conductivity: The thermal diffusion coefficient of the material is determined by the laser flash method, and the thermal conductivity is calculated by combining the specific heat capacity and density of the material. The test equipment is a laser thermal conductivity meter. Before the test, the sample is processed into a disc with a diameter of 12.7mm and a thickness of 2-3mm;

[0060] Tensile strength: According to GB / T1040.2-2006 standard, the test was carried out using an electronic universal testing machine. The injection molded specimens were made into a standard dumbbell shape, and the tensile speed was set to 50 mm / min.

[0061] Bending strength: According to GB / T9341-2008 standard, the test was carried out on an electronic universal testing machine, with the sample size of 80mm×10mm×4mm, the span of 64mm, and the loading speed of 2mm / min;

[0062] Anti-aging performance: The xenon lamp aging test is used to simulate light aging in the natural environment. The specimens are placed in a xenon lamp aging test chamber, and the test conditions are set according to GB / T16422.2-2014 standard. The aging time is 1000h. The tensile strength is tested before and after aging, and the tensile strength retention rate is calculated to evaluate the anti-aging performance.

[0063] Table 1. Nylon material performance test data table

[0064]

[0065]

[0066] As shown in Table 1, experiments show that Example 1 has the best comprehensive performance in terms of thermal conductivity, strength and anti-aging performance. The synergistic effect of its dual matrix system, specific high thermal conductivity filler combination, filler pretreatment and additive addition is significantly better than the single nylon matrix and different filler combination system of Comparative Example 1, and the simple system of Comparative Example 2 containing only ordinary fillers and no anti-aging additives.

[0067] Finally, it should be noted that: Obviously, the above embodiments are only examples for clearly explaining the present invention, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the scope of protection of the present invention.

Claims

1. A high thermal conductivity nylon material, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of nylon, 20-30 parts of polybutylene terephthalate, 17-24 parts of high thermal conductive filler, 0.8-1.3 parts of antioxidant, 0.3-0.5 parts of light stabilizer, 3-5% of the total mass of nylon and polybutylene terephthalate, and 1-2% of the coupling agent of the high thermal conductive filler; The high thermal conductive filler is composed of 15-20 parts of aluminum nitride and 2-4 parts of carbon nanotubes; The antioxidant is composed of 0.5-0.8 parts of hindered phenol antioxidant AO-80 and 0.3-0.5 parts of phosphite antioxidant 121; The light stabilizer is selected from hindered amine light stabilizer 944; The compatibilizer is maleic anhydride grafted polypropylene; The coupling agent is silane coupling agent KH560 ethanol solution.

2. A method for preparing a high thermal conductivity nylon material, characterized in that: A high thermal conductivity nylon material as claimed in claim 1, comprising the following method steps: S1. Filler pretreatment: S1-1, placing aluminum nitride and carbon nanotubes in a vacuum drying oven respectively, and drying at 120-130° C. for 6-8 hours to remove moisture; S1-2, adding the dried aluminum nitride and carbon nanotubes to 1-2% silane coupling agent KH560 ethanol solution respectively, ultrasonically dispersing for 45-60 minutes to make the coupling agent evenly coated on the surface of the filler, and then drying at 80-90° C. for 8-10 hours to obtain a pretreated filler; S2. Premixing of base and additives: S2-1, drying the nylon slices and the polybutylene terephthalate slices in a blast drying oven to remove moisture; S2-2, weigh the dried nylon, polybutylene terephthalate, pretreated filler, antioxidant, light stabilizer and compatibilizer according to the proportion, add them into a high-speed mixer, and mix them at a speed of 600-800 r / min for 15-20 min to preliminarily mix the components evenly; S3, melt blending: adding the premixed materials into a twin-screw extruder for melt blending; S4, granulation and molding: the material extruded from the twin-screw extruder is water-cooled and drawn into a pelletizer for granulation to obtain pellets of high thermal conductivity and anti-aging nylon composite materials.

3. The method for preparing a high thermal conductivity nylon material according to claim 2, characterized in that: In the step S2-1, nylon is dried at 90-100°C for 8-10 hours, and polybutylene terephthalate is dried at 110-120°C for 6-8 hours.

4. The method for preparing a high thermal conductivity nylon material according to claim 2, characterized in that: In the step S3, the temperature of the twin-screw extruder is set as follows: zone 1 temperature 230-240°C, zone 2 temperature 240-250°C, zone 3 temperature 250-260°C, zone 4 temperature 260-270°C, zone 5 temperature 270-280°C, die head temperature 260-270°C, screw speed 300-400r / min, and the material residence time in the extruder is about 4-6min.

Citation Information

Cited By

  • High-molecular thermal conductive plastic based on graphene modification and preparation method of high-molecular thermal conductive plastic

    CN120623765A